Post-COVID-19 related osteonecrosis of the jaw (PC-RONJ): an alarming morbidity in COVID-19 surviving patients - Haytham Al-Mahalawy; Yehia El-Mahallawy; Noha Y. Dessoky; Sally Ibrahim; Hatem Amer; Haytham Mohamed Ayad; Hagar Mahmoud El Sherif; Alshaimaa Ahmed Shabaan (BMC Infectious Diseases, 2022)
Abstract Purpose The recent coronavirus disease (COVID-19) pandemic mainly affects the respiratory system; however, several oral and maxillofacial post-COVID-19 complications have also been observed. This series reports the growing number of osteonecrosis cases associated with post-COVID-19 patients. Materials and methods This is a retrospective, multi-center case series that reports cases with maxillary osteonecrosis after various periods of SARS-CoV-2 infection in the period between January and August 2021 based on the PROCESS guidelines. Results Twelve cases were reported with post-COVID-19 manifestation of spontaneous osteonecrosis of the maxillary jaw. Five patients were hospitalized during COVID-19 management and all of the twelve cases had at least one systematic Co-morbidity, and undertake corticosteroids prescription based on the COVID-19 disease treatment protocol. The mean onset of osteonecrosis symptoms appearance was 5.5 ± 2.43 weeks calculated from the day of the negative PCR test. The management was successfully done through surgical debridement and pre and post-operative antibiotics. No anti-fungal medications were prescribed as the fungal culture and the histopathological report were negative. Conclusion Post-COVID-related osteonecrosis of the jaw (PC-RONJ) could be now considered as one of the potential post-COVID-19 oral and maxillofacial complications that occurs unprovokedly and mainly in the maxilla.